Asuhan Keperawatan Pada Ny. S & Ny. E yang Mengalami Risiko Infeksi Post Partum Sectio Caesarea dengan Indikasi Bayi Letak Lintang di Ruang Dahlia RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Sindu, Karmila; Agustina, Agustina; Prihatini, Fitria (STIKes Persada Husada Indonesia, 2024)
Post partum caesarean section is a surgical procedure to deliver the fetus through an incision in the abdomen and uterine wall. The post partum period is a period of recovery, starting from the end of labor until the uterus returns to its pre-pregnancy state. Nursing care for clients who are at risk of infection in post partum caesarean section which will be carried out on April 10 - April 14 2023. This research method is descriptive qualitative, with the aim of obtaining an overview of the implementation of client data in nursing care for clients who are at risk of infection in post partum sectio caesarea in the Dahlia and Ponek rooms at RSUD dr. Chasbullah Abdulmadjid Bekasi City. This research was carried out using a nursing care approach which includes assessment, diagnosis, planning, implementation, evaluation and documentation with data collection carried out through physical examination, interviews and observation. From the nursing care provided, there were 5 nursing diagnoses for Mrs. S and 4 nursing diagnoses for Mrs. E. There was only one difference in diagnosis in Mrs. S, namely a knowledge deficit about baby care, while in Mrs. E there was no diagnosis of a knowledge deficit about baby care. At the evaluation stage, the diagnosis of Mrs. S and Mrs. E was carried out according to the planning and the final evaluation was completed according to the 3x24 hour time criteria. Collaborative administration of antibiotics such as ceftriaxone with a dose of 1 gram then changing the bandage 3 days post sc and recommending consuming foods high in protein such as (egg whites) which has been carried out by researchers has proven to be effective in helping to overcome the risk of infection in both clients, Mrs. S and Mrs. E.